2005
DOI: 10.1145/1070838.1070867
|View full text |Cite
|
Sign up to set email alerts
|

For mobile applications, branding is experience

Abstract: Mobile technology is everywhere---with new types of mobile devices appearing regularly. While branding of the devices themselves can draw upon a long history of product branding, the branding of mobile applications presents new questions and challenges. I became aware of some of these challenges during InContext Enterprises' development of the mSports mobile sports application, which allows users to follow the play-by-play action of Major League Baseball on a variety of mobile phones. We gathered customer data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 5 publications
1
31
0
Order By: Relevance
“…In the broad sense, these beliefs define the cognitive structure and constitute consumer expertise (Alba & Hutchinson, 1987). Consumer perceptions about a brand's physical, functional and utilitarian attributes contribute to brand experience (Gentile et al, 2007;Rondeau, 2005;Tynan & McKechnie, 2009). Yet, the verbal cues are important stimuli enhancing consumer brand experiences.…”
Section: Attribute Perceptionmentioning
confidence: 99%
“…In the broad sense, these beliefs define the cognitive structure and constitute consumer expertise (Alba & Hutchinson, 1987). Consumer perceptions about a brand's physical, functional and utilitarian attributes contribute to brand experience (Gentile et al, 2007;Rondeau, 2005;Tynan & McKechnie, 2009). Yet, the verbal cues are important stimuli enhancing consumer brand experiences.…”
Section: Attribute Perceptionmentioning
confidence: 99%
“…Research has found usability to be the most significant source of frustration for mobile internet users, indicating the importance of usability in determining customers' perceived quality of an m-commerce web site (Venkatesh et al, 2003). Rondeau (2005) argues that a positive experience using mobile applications, as a result of positive usability, can lead to positive consumer evaluation of the quality of the applications and can be translated by the consumer into a favorable associations towards the brand. Tarafdar and Zhang (2007) empirically confirm that usability has a significant positive impact on loyalty to a web site.…”
Section: M-commerce Attributes and Brand Equitymentioning
confidence: 99%
“…Rondeau [9] provides insight on the importance of branding and how it relates to mobile applications. He discusses the challenges of branding an application on a mobile device which features many competing brands itself.…”
Section: Related Workmentioning
confidence: 99%